IMPLEMENTASI PROGRAM WAJIB BELAJAR 9 TAHUN DI PEKANBARU TAHUN 2012 - Anti, Aspri; Rusli, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Indonesian government step in addressing issues of educational equity, namely the launching of 9-Year Compulsory Education Program set forth in Government Regulation No. 47 of 2008 on compulsory education. One of the problems facing the city of Pekanbaru in 2012 in the field of education that is not maximal implementation of the 9-year compulsory education program. Therefore the Government Pekanbaru required to pay attention to children of school age is 7-15 years to follow the 9-year compulsory education program. The main problem that often arises in the success of compulsory nine-year program is to ensure that children who have graduated from primary school to continue their education through programs to level junior or package B. All school-age children can menyenyam education if the educational facilities available. This condition cannot be separated from Pekanbaru city government in facilitating the participation of educational facilities.This study aims to determine the Implementation of Compulsory 9 Year In pekanbaru In 2012 and examine the factors that affect the implementation of 9-year compulsory education program in Pekanbaru In the Year 2012.From the results of research and analysis concluded that the implementation of the 9-year compulsory education program can be seen from each of the indicators of the study variables namely: 1 standards and targets. 2. Resources. 3. communication between organizations. 4. Characteristics of the implementing agency. 5. Social and economic conditions. 6. Disposition. Factorsthat affect the implementation of 9-year compulsory education program, namely 1. Human resources, 2. Fund, 3. FacilityKeywords: implementation, program, Compulsory 9 year 2012